ANALISA PENURUNAN DAYA HISAP POMPA PENDINGIN MOTOR INDUK PADA KAPAL MV.BAHARI 22 DAN ALTERNATIF PEMECAHANNYA - Iswanda; Trisno Susilo (JURNAL JALASENA, 2020)
The pump is a machine for moving fluid. The pump moves fluid from a low pressure place to a place with a higher pressure, to overcome this pressure difference a power is needed. The cooling system is a system that serves to keep the engine temperature in ideal conditions.Seawater cooling pump used on the MV.BAHARI 22 ship, experienced a problem of decreased suction power analyzed using quantitative research methods in which research uses data taken directly on the ship. Then the analysis of this study uses a predetermined formula. Research findings and analyzed data are head loss which includes static head, head pressure, head speed, head major loss, head minor loss. The decrease in the pressure of the sea water coolant pump on the ship is caused by the total head of the system which exceeds the pump head where the head of the system according to the calculation is 61 m, while the maximum head of the pump is only 55 m so that the cavitation in the pump is ensured which causes impeller damage and damages the house the snail This can be proven from the calculation results where the NPSHr value = 5.49 meters far exceeds the NPSHa value which is only 2.52 m.